Analysis of the collagen fibers on autopsied patients' uterus with the Acquired Immunodeficiency Syndrome - Bianca Gonçalves Silva Torquato; Mariana Silva Oliveira; Guilherme Ribeiro Juliano; Laura Sanches Aguiar; Gabriela Ribeiro Juliano; Luciano Matias da Silveira; Ana Paula Espíndula; Lívia Ferreira Oliveira; Camila Lourencini Cavellani; Flávia Aparecida de Oliveira; Vicente de Paula Antunes Teixeira; Mara Lúcia Fonseca Ferraz
Abstract Objectives: to compare the percentage of collagen fibers in the autopsied women's uterine body and cervix with and without the Acquired Immunodeficiency Syndrome (Aids). Methods: 30 autopsied women's medical files were selected from 1988 to 2013. 30 fragments of the uterine body and 30 cervix were collected and then divided into two groups, 15 with Aids and 15 without, The quantification of the collagen fibers of the uterine body and cervix was performed on slides stained with picrosirius, using the KS-300® system. Results: the percentage of collagen fibers was lower for cervix (U=336544; p=0.001) and higher for the uterine body (U=308726,5; p=0.004) in the retroviral group when compared to the group without the disease. The percentage was higher for cervix than the uterine body in the group with Aids (t=0,4793; p=0.0031). the same result was found in the group without Aids (t=2,397; p=0.0637). Conclusions: the increase in the percentage of collagen fibers in the uterine body of women with Aids' indicates an immune response for viral infection and reveals a failure in keeping the infection restricted to the cervix. The interpretation of the histochemical and morphometric parameters can be useful in the diagnosis associated to HIV infection, contributing for clinical improvement and life expectancy.